2006
DOI: 10.1002/bip.20630
|View full text |Cite
|
Sign up to set email alerts
|

Differential recognition of natural and nonnatural substrate by molecular chaperone α‐crystallin—A subunit exchange study

Abstract: Abstractα‐Crystallin is a molecular chaperone that recognizes proteins substrates in stress. It binds to the unstable conformer of a large variety of related or unrelated substrates and thus prevents them aggregating and holds them in a folding competent state. In this article, we have tried to critically analyze, from experimental point of view, whether α‐crystallin has any preference for its natural substrates compared to the nonnatural one. Our results clearly show that α‐crystallin is exceptionally active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…Recently we demonstrated that subunit exchange rate can be a valid mechanism by which a-crystallin can distinguish between the native and non-native substrate. 75 Results presented here ( Figure 8 and unfavorable for keeping the chaperone-substrate interaction soluble folding competent state. It appears to us that the subunit exchange rate is in someway related to the major b-sheet content of the wild type protein.…”
Section: Role Of N-terminal Region In Chaperone Function Of -Crystallmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently we demonstrated that subunit exchange rate can be a valid mechanism by which a-crystallin can distinguish between the native and non-native substrate. 75 Results presented here ( Figure 8 and unfavorable for keeping the chaperone-substrate interaction soluble folding competent state. It appears to us that the subunit exchange rate is in someway related to the major b-sheet content of the wild type protein.…”
Section: Role Of N-terminal Region In Chaperone Function Of -Crystallmentioning
confidence: 95%
“…These two probes have been previously characterized and used to monitor exchange of subunits. 50,51,54,55,75 FðU The subunit exchange reaction was initiated 50 by mixing an equimolar concentration of the donor (AIAS) with the acceptor (LYI) labeled mutant at 378C. AIAS emission intensity at 415 nm is decreased in a time dependent manner (Figures 8A and 8B) with a concomitant increase in intensity at 525 nm indicating FRET because of the close proximity of LYI and AIAS.…”
Section: Effect Of N-terminal Deletion On Subunit Exchangementioning
confidence: 97%
See 1 more Smart Citation
“…32,33 We earlier reported that subunit exchange rate of aA-crystallin decreased significantly when non-natural substrate was bound to it 33 or when its N-terminal region was deleted. 26 Since intersubunit metal ion bridge formation is expected to influence the subunit exchange rate, we decided to measure the same in aA-crystallin in presence and absence of Zn 12 using FRET.…”
mentioning
confidence: 98%
“…In order to carry out the FRET study recombinant aA-crystallin was separately labeled with AIAS and LYI through available cystein residues. 32,33 Recombinant human aA-crystallin contains two cystein residues at positions 131 and 142 among which the first one is exposed while the later is buried. We did not use human aB-crystallin because it did not contain any cystein residue.…”
mentioning
confidence: 99%